Determinação de elementos traços na água e no sedimento do baixo curso da Bacia do Itapecuru-MA, Brasil - SILVA, Francisco Eduardo Paiva Silva e (2018)
Responsible for supplying 55% of the population of the capital São Luís, Maranhão, the Itapecuru river basin has always been essential for the development of the region. Though, anthropogenic impacts due to uncontrolled population growth and agricultural expansion have led to changes in water quality. This study aimed to evaluate the physical-chemical parameters in water and trace elements (Al, Cd, Cr, Fe, Mn, Pb, Se and Zn) in surface water and sediments in the lower Itapecuru river in three cities (Rosário, Santa Rita and Itapecuru-Mirim), and it was conducted during the dry and wet seasons to understand the frequency of pollution throughout the year. In relation to the limits established by Brazilian legislation, the results of the physical-chemical analysis of the water for the wet season qualify it for human consumption, whereas for the dry season, inadequacies are observed in the turbidity(102 – 165 NTU), dissolved oxygen (4.10 – 4.36 mg.L-1 ) , total dissolved solids (2 – 6.64 g.L-1 ) and salinity (0.18 – 0.65 PPT), mainly in the city of Rosário. In water samples the concentration of Al and Fe were higher than the allowed at all sampling points during the dry season (0.17 – 1.18 mg.L-1 Al ; 1.18 – 3.70 mg.L-1 Fe), as well as in the cities of Rosário and Itapecuru-Mirim, during the wet season (0.18 – 0.39 mg.L-1 Al ; 0.77 – 2.02 mg.L-1 Fe). In conclusion, the results suggest a significant seasonal effect (p < 0.05) on water and sediment samples, and the concentrations found are likely to cause adverse effects to aquatic biota and man.